Model of shear test for tearing strength of concrete - Yu. V. Krasnoshchekov (Вестник СибАДИ)
Introduction. To control the concrete strength of reinforce concrete structures the shear test based on the empirical proportional dependence of concrete strength and tear force of a special purpose anchor with an expanding cone is used. The absence of a physical model of a concrete deterioration when tearing strength is a sign of the defect of the method which hampers the search of the ways for accuracy increase and test validity. The purpose of this study is to develop a physical model of concrete deterioration to determine the calculated strength by the shear test.Materials and methods. The concrete strength model is a mechanism for local deterioration by tearing out a body of concrete in the form of an indicative cone when extracting it from a pre-fabricated anchor well. It is accepted that the deterioration occurs in two stages: from the melting of the concrete to the formation of cracks in the plane of the apex of the concrete cone in the first stage and the subsequent formation of cracks along the lateral surface of the cone during the extraction of the anchor. For transition to compression resistance, the average of the ratio of concrete resistance to compression and tensile or Fere formula shall be used. The model was verified by the calculation of 6 test measurements.Conclusions. It has been established that the empirical correlation between the resistance of concrete to compression and the force of extraction of the anchor in the concrete test is only possible if the resistance of concrete is linearly related to compression and extension. However, the actual ratio of concrete resistance to compression and tensile is non-linear, so for relatively weak concrete the possibility of overestimating the strength of concrete on compression empirical dependence is offset by a reduction factor, and for more durable concrete, measurements are underestimated.